Correlation of sub18F-FDG-PET and histopathology in patients with malignant melanoma - Bohuslavizki, Karl H. (Radiology and oncology (Ljubljana), 2000)
Background. Preliminary reports suggest that PET using 18F-FDG may be a valuable diagnostic tool in patients with advanced malignant melanoma. Therefore, the aim of this study was to correlate PET lesions with histological findings in staging of malignant melanoma. Patients and methods. A total of 82 patients with malignant melanoma underwent 107 PET examinations for primary staging or therapy monitoring. After an intravenous injection of 370 MBq18F-FDG whole-body images were acguired on an ECAT EXACT 47 (921) with an axial field-of-view of 16.2 cm (Siemens, CTI). Tumor-suspicious PET findings, results of physical examination, and tumor-suspicious lesions by conventional imaging, i.e. ultrasound, CT, and MRl, were evaluated histologically and correlated with each other on a lesion-by-lesion basis. Results. PET detected 124 lesions with an increased focal tracer uptake. In addition, physical examination and conventional imaging revealed 65 tumor-suspicious lesions. In total, 189 tumorsuspicious lesions were evaluatedhistologically. 18F-FDG-PET was hue-positive in 115/189 lesions and false-positive in 9/189 lesions. In 21 out of 65 PET-negative lesions, biopsy could not confirm melanoma tissue. In contrast, in 44 out of 65 PET- negative lesions further biopsy revealed malignant melanoma tissue. Sensitivity and specificity of 18F-FDG-PET for the detection of malignant melanoma tissue were72% and 70%, respectively. Negative and positive predictive values of 18F-FDG-PET imaging were 32% and 93%, respectively. With respect to anatomicallocalization, two thirds of false negative/positive PET lesions werelocated in the skin or mucosal area. Conclusions. 18F-FDG-PET is a valuable diagnostic tool in order to prove tumor- suspicious lesions in malignant melanoma. However, for exclusion of skin metastases an accurate physical examination of patients with malignant melanoma by a dermatologist isindispensable. (Abstract truncated at 2000 characters.)
Keywords: Deoxyglucose; Diagnosis; diagnostika; Fluorine; histologija; kožne bolezni; melanom; Melanoma; Neoplasm metastasis; Neoplasm staging; Pathology; radiologija; rak (medicina); Tomography, emission-computed